(untitled) (Training and Practice : Journal of Educational Sciences, 2011)
After the Austro-Hungarian Compromise of 1867, the Hungarian society changed and there was an increasing demand for women’s general and skill education at an appropriate level, just like men. Before grammar schools for girls were established, girls had found few opportunities to be qualified at secondary level. Thus, in this era, girls could pursue studies at higher than elementary level at four-grade practical schools for girls (1868), which had the aim to prepare students for practical life in addition to provide general education; also at upper grade all-female schools (1875), which belonged either to public primary education or to secondary education at the time. These upper grade schools, not considered as secondary schools, were placed sonder the authority of public school inspectors in 1887. Not much later, the order of 1901 regarded upper grade all-female schools as secondary schools again. They were transformed into seven-grade schools in 1916, with their lower forms being unified, while there were three types of upper forms: commercial classes, upper grade all-female school classes, and grammar school classes.